Ultrasound therapy reduces persistent post-thoracotomy tactile allodynia and spinal substance P expression in rats. Issue 5 (21st March 2019) - Lin, Heng-Teng; Chiu, Chong-Chi; Liu, Chen-Chih; Chen, Yu-Wen; Wang, Jhi-Joung; Hung, Ching-Hsia
Abstract : Background: Therapeutic ultrasound (TU) alleviates nerve injury-associated pain, while the molecular mechanisms are less clear. This is an investigator-initiated experimental study to evaluate the mechanisms and effects of ultrasound on prolonged post-thoracotomy pain in a rodent model. Methods: The rats were randomly separated into four groups (n=8 per group): sham-operation (sham; group 1), thoracotomy and rib retraction (TRR; group 2), and TRR procedure followed by TU (TRR+TU-3; group 3) or TU with the ultrasound power turned off (TRR+TU-0; group 4). TU was delivered daily, beginning on postoperative day 11 (POD 11) for the next 2 weeks. Mechanical sensitivity, subcutaneous tissue temperature, and spinal substance P and interleukin-1 beta (IL-1β) were evaluated on PODs 11 and 23. Results: Group 3, which received ultrasound treatment (3 MHz; 1.0 W/cm 2 ) for 5 min each day, demonstrated higher mechanical withdrawal thresholds when compared with the group without ultrasound intervention (group 2) or sham ultrasound (group 4). Ultrasound treatment also inhibited the upregulation of spinal substance P and IL-1β measured from spinal cord dorsal horns extract and increased subcutaneous temperature. Conclusions: The results of this study suggest an increase in mechanical withdrawal thresholds and subcutaneous temperature, as well as a downregulation of spinal substance P and IL-1β, in the group which received ultrasound treatment. The regulation of spinal substance P and IL-1β may mediate potential effects of this non-invasive treatment.